Teaching of National Symbols as a Costa Rican Identity in a Globalized World - Cerdas Chaves, Nazareth (2022)
This article is the result of a critical reflection on the commercialization of national symbols and their relationship with education. In the process of globalization, the incorporation of new symbols has been the result of a strategy that aims to increase Costa Rica's exposure in the world. Therefore, teaching them requires a mediation that guides the process of building an identity, through a critical conscience that questions and analyzes each national symbol in the context in which they were decreed. After the above, the meaning of symbols will be understood in contrast to their use as part of competitiveness and government marketing. It is a challenge for Civic Education teachers to teach elements linked to nationalism and politics, which also allow the identification of individuals with a collective conscience.